THE INFLUENCE OF COMPETENCE AND WORK ETHIC ON EMPLOYEE PERFORMANCE AT PT. PERMODALAN NASIONAL MADANI MEKAR BRANCH PADANG - Dewi, Mirna; Pratikno, Yuni; Jati, Prihatina (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
Population in this study is PNM Mekar Pekanbaru Branch employees totaling 100 people, The number of samples taken is 71 employees of PT. Madani Mekaar National Capital, Padang Branch as a respondent in this study. the calculated t value for Competence (X1) is 4.858 while the t table value for n = 71 is 1.950. So 4.858 > 1.950, then H0 is rejected and Ha is accepted, it can be stated that Competence (X1) has a significant effect on Employee Performance (Y), the calculated t value for Work Spirit (X2) is 9.758 while the t table value for n = 71 is 1.950. So 9.758 > 1.950, then H0 is rejected and Ha is accepted, it can be stated that Work Spirit (X2) has a significant effect on Employee Performance (Y), From the results of the analysis in the table above, namely the ANOVA test, the F calculated value is 97.976, while F table ( 0.05) for n = 71 is 3.312. So Fcount > from Ftable ( 0.05) or 97.976 > 3.312 with a significant level of 0.000 because 0.000 < 0.05, then it can be said that Competence (X1) and Work Spirit (X2) together have a positive effect on Employee Performance (Y). The R Square (R2) value is 0.742. This shows that 74.2% of Competence (X1) and Work Spirit simultaneously affect Employee Performance (Y) while the remaining 25.8% is influenced by other factors not examined in the study.